The soul, the mind, and the psychoanalyst : the creation of the psychoanalytic setting in patients with psychotic aspects - Rosenfeld, David, ....- (London : Karnac, 2006)
This book is based on various cases whose common factor is how the psychoanalytic setting is created: the internalization and realization inside the patient's mind: with the feeling of fixed hours and the transferential relation with the psychoanalyst. Referring to the great masters of psychoanalysis, Rosenfeld guides us step by step through the mysterious terrain of the mind, especially in its most regressive, primitive and psychotic aspects.
Includes bibliographical references (p. 239-250) and index.
Keywords: Psychoanalyse; Psychosen